Determination of a full range constitutive model for high strength S690 steels. (November 2020) - Ho, H C; Xiao, M.; Hu, Y.F.; Guo, Y.B.; Chung, K.F.; Yam, M.C.H.; Nethercot, D.A.
Abstract: In order to enable accurate analysis and prediction on structural behaviour of high strength S690 steel member at large deformations, an integrated experimental, theoretical and numerical investigation to formulate a full range constitutive model is reported in this paper. It is well known that standard tensile tests are effective means to obtain key mechanical properties of coupons for deformations up to on-set of necking. However, owing to non-uniform cross-sectional distributions in both stresses and strains within the necking regions of the coupons, it is important to allow for these effects when analysing measured forces and extensions to give true stresses and strains of the coupons. The proposed instantaneous area method has been developed and calibrated against test results of a total of 30 standard tensile tests on S690 cylindrical coupons, and it is formulated with key mechanical properties of engineering stress-strain curves readily obtained from these tests. High resolution digital images of the deformed coupons are captured and analysed to obtain instantaneous dimensions of the necking areas. Through theoretical formulation, true stress-strain curves of the coupons after on-set of necking are derived, and modified with numerical correction factors through successive approximations. After normalization on all the corrected true stress-strain curves, a set of formulae to describe the full-range constitutive model for the high strength S690 steels is proposed. Consequently, the proposed model is readily applicable to both analytical and numerical analyses of the high strength S690 steels and their structural members undergoing both small and large deformations up to fracture. Highlights: Full range true stress-strain curves of the S690 steels up to fracture are determined using the instantaneous area method. The effects of non-uniform stress and strain distributions of the test coupons after onset of necking is accounted for. The corrected true stress-strain curves are fully calibrated against 30 sets of measured test data. A constitutive model for the S690 steels under monotonic action is proposed after a comprehensive validation. The proposed constitutive model is readily applicable to structural analyses on high strength S690 steel structures.